2018
DOI: 10.1109/tuffc.2018.2869473
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time High-Frame-Rate Cardiac B-Mode and Tissue Doppler Imaging Based on Multiline Transmission and Multiline Acquisition

Abstract: Cardiovascular diseases, the leading cause of death in the world, are often associated with the dysfunction of the left ventricle. Even if, in clinical practice, the myocardial function is often assessed through visual wall motion scoring on B-mode images, quantitative techniques have been introduced, e.g. ultrasound tissue Doppler imaging (TDI). However, this technique suffers from the limited frame rate of currently available imaging techniques that needs to be balanced with the field of view. High frame rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Instead, it would be preferable implementing smarter imaging modes that could achieve, in real-time, the same FRMax but with an improved quality of images. For example, since the current architecture of the ULA-OP 256 system allows reconstructing up to 32 lines per transmission event, when being limited by PRFMax [43] in real-time cardiac applications, SPT is too much demanding (100 lines per transmission event) and a different transmission scheme should be implemented. An option could be the transmission of diverging waves having narrower aperture angles to scan each plane in several (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it would be preferable implementing smarter imaging modes that could achieve, in real-time, the same FRMax but with an improved quality of images. For example, since the current architecture of the ULA-OP 256 system allows reconstructing up to 32 lines per transmission event, when being limited by PRFMax [43] in real-time cardiac applications, SPT is too much demanding (100 lines per transmission event) and a different transmission scheme should be implemented. An option could be the transmission of diverging waves having narrower aperture angles to scan each plane in several (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In general, continuous real-time HFR imaging is beneficial when subsequent processing is applied to produce additional information in real-time, e.g. tissue-motion [43] or color flow imaging [69]. For example, through the implementation of a speckle tracking technique, the frame rate achieved in this work with SPT and MPT (250 Hz) might enable real-time functional analysis of all left ventricular segments of the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsically, crosstalk artifacts are the results of the interference between MLT beams in different directions. It has been demonstrated that such crosstalk artifacts can be largely suppressed by using a Tukey (α = 0.5)-Tukey (α = 0.5) (TT) transmit and receive apodization scheme; so that the resulting MLT images look competitive to the conventional single line transmit beamforming (SLT) ( Figure 2b) [8,9,11]. Nonetheless, despite these promising results, residual crosstalk artifacts can sometimes be detected [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since MLT is prone to cross-talks, many studies focused on reducing the image artifacts [16], [17], [14]. Although tissue Doppler imaging (TDI) has been applied to MLT images [18], [19] this beamforming method has received little attention in motion estimation.…”
Section: Introductionmentioning
confidence: 99%